1999
DOI: 10.1046/j.1365-2168.1999.0696c.x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative renal function following endovascular repair of abdominal aortic aneurysm with suprarenal and infrarenal stents

Abstract: BACKGROUND: Endovascular repair (EVR) of abdominal aortic aneurysm (AAA) is feasible for selected patients. Placing an uncovered stent across the origins of the renal arteries may improve fixation and seal of the proximal end of the stent-graft. However, this has potential for problems (e.g. renal artery stenosis or microembolization). This study aimed to evaluate the short-term effect of a suprarenal stent on the function of the individual kidney. METHODS: In 30 patients undergoing EVR for AAA, renal function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 0 publications
1
16
1
1
Order By: Relevance
“…Macierewicz et al reported the evaluation of 30 EVAR patients with IR (11) and SR (19) fixation studied by postoperative technetium-labeled diethylene triamine penta-acetic acid (Tc-DTPA) scans and reported that coverage of renal ostia by bare struts did not effect on renal function. 30 Greenberg et al compared 80 open AAA repair patients with 190 patients undergoing EVAR with SR fixation using different definitions of renal dysfunction. 15 EVAR patients had less renal dysfunction prior to hospital discharge than OR patients; subsets of both groups had renal dysfunction prior to discharge and up to 12 months, but they reported that this "stabilized or improved at 12 to 24 months".…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Macierewicz et al reported the evaluation of 30 EVAR patients with IR (11) and SR (19) fixation studied by postoperative technetium-labeled diethylene triamine penta-acetic acid (Tc-DTPA) scans and reported that coverage of renal ostia by bare struts did not effect on renal function. 30 Greenberg et al compared 80 open AAA repair patients with 190 patients undergoing EVAR with SR fixation using different definitions of renal dysfunction. 15 EVAR patients had less renal dysfunction prior to hospital discharge than OR patients; subsets of both groups had renal dysfunction prior to discharge and up to 12 months, but they reported that this "stabilized or improved at 12 to 24 months".…”
Section: Discussionmentioning
confidence: 99%
“…11-20 ; (3) among patients undergoing EVAR, is there a difference in the development of renal function deterioration following infrarenal (IR) vs suprarenal (SR) fixation? [14][15][16][21][22][23][24][25][26][27][28][29][30] ; (4) do surveillance CT scans contribute to renal function deterioration after EVAR? 16 ; (5) what are the risk factors for declining renal function after EVAR and OR?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Renal function and perfusion remain unaffected in suprarenal placement of stent-grafts. [7][8][9] In our study there were two patients with AAA and unilateral RAS and one patient with AAA and solitary-functioning kidney with RAS.…”
Section: Discussionmentioning
confidence: 90%
“…So far the presence of the suprarenal stent does not appear to impair kidney function. 2,8 Complications of the endovascular repair of AAA include graft migration and endoleak. Probably improved graft design will secure longterm durability of this procedure.…”
Section: Discussionmentioning
confidence: 99%